Synthesis, characterization and ethanol sensing properties of carboxylic acid-terminated naphthoxy substituted phthalocyanines - Isik, Seher Neccaroglu; Karaoglan, Gulnur Keser; Omur, Birsel Can; Altindal, Ahmet; Kose, Gulsah Gumrukcu (ELSEVIER SCIENCE SA, 2018)
A new mono substituted phthalonitrile derivative of 4-(6-carboxy-2-naphthoxy)phthalonitrile was prepared by a nucleophilic displacement reaction of 4-nitrophthalonitrile with 6-hydroxy-2-naphthoic acid. Metallophthalocyanines of [2,9,16,23-tetra-(4-(6-carboxy-2-naphthoxy)-phthalocyaninato-zinc(II)], cobalt(11), copper(II), nickel (II), and metal free phthalocyanines bearing carboxylic acid groups at the peripheral positions have been designed and synthesized by cyclotetramerisation of the phthalonitrile to investigate the influence of the central metal atom on the ethanol vapor sensing properties. All newly synthesized compounds were characterized by UV Vis, FTIR, H-1-NMR, MALDI-TOF MS and elemental analysis spectral data. The influence of COOH group on the organic vapor sensing performance towards 5 different groups of analytes (alkanes, chlorinated hydrocarbons, amines, alcohols and aromatics) were examined. Ethanol adsorption onto the thin films of these compounds and the effects of operating temperature on the sensing properties were also studied. The sensing data show that all the films of phthalocyanine compounds show response to ethanol, among which, [2,9,16,23-tetra-(4-(6-carboxy-2-naphthoxy)-phthalocyaninato-nickel (II)] based sensor show the highest response, demonstrating central metal atom dependence of ethanol sensitivity. Surface topography of the sensing films were analyzed by atomic force microscopy.
Keywords: Phthalocyanine; Carboxylic acid; Naphthol; Ethanol sensing; Response time; Sensitivity; COPPER PHTHALOCYANINE; THIN-FILMS; ORGANIC VAPORS; METAL-FREE; ADSORPTION; TIO2; METALLOPHTHALOCYANINES; SENSORS; SINGLE; NICKEL; Materials Science; Physics; Polymer Science